Rural youth attitudes towards immigrants - Somerkoski, Saaga (Finnish Journal of eHealth and eWelfare, 2021)
The aim of this study is to research the attitudes towards immigrants among rural Finnish second grade students. The study was carried out in Southern Ostrobothnia region which is strongly countryside and where the number of immigrants is the lowest in Finland. Also, the level of education in the region is the lowest in Finland. During the next decades, immigrants will be an important source of labour, since the population in Finland is getting older - faster than in any other European country. The data (n=275) was collected from colleges and upper secondary schools. The analysis showed that gender, parents level of education and the multicultural connections had an effect on persons attitudes towards immigrants. Youths´ attitudes also varied towards different immigration groups and nationalities. Attitudes towards the immigration of children and labour for example, were more positive than attitudes towards unemployed migrants and refugees. In terms of nationalities, Western immigrants were more positively welcomed than immigrants from war zones and those from the crisis areas. Answers to the open-ended question in the end of the questionnaire showed that the attitudes towards immigration were particularly concerned with refugees and the policy of immigration. Open answers included both racist and negative statements as well as statements to helping refugees. The results of this study may be of use when the new refugee policies are implemented in near future. The increase in immigrant labour requires respect, cooperation and cultural tolerance. To stabilize the economy in Finland and to be able to work in the future, new, more tolerant attitudes are needed.